Análise comparativa das variáveis micrometeorológicas, de solo e fluxos de massa e energia, dos ecossistemas Pantanal e Cerrado em Mato Grosso Brasil - Justi, Jamson (2023)
Monitoring and understanding the behavior of micrometeorological variables, soil and energy fluxes in different biomes is of paramount importance, given the changes that constantly occur in the environment. This work aims to compare data from two ecosystems in the state of Mato Grosso, they are: Baía das Pedras (Pantanal, with data from 2014 to 2016) and Fazenda Miranda (Cerrado dirty field, with data from 2011 to 2013), and to understand which, or which variables, whether from the atmosphere or soil, most influence the fluxes of GPP (gross primary productivity), NEE (net exchange of 2 in the ecosystem) and ET (evapotranspiration). It also discusses the influence and relationship between deforestation and fires in ecosystems in the feedback of water in the atmosphere through a causal loop diagram (DLC). The methodology used in this work, in relation to the method of approach, is the hypothetical-deductive method, and in relation to the method of procedure, the statistical and comparative methods were used. By normalizing the data, it was found that the relative humidity was higher in the Pantanal ecosystem. In the Cerrado, especially in the final periods of drought, very low humidity was observed. Regarding air temperatures, it should be noted that they are higher in the Cerrado, notably in August of the second year. In January of the third year, equivalent temperatures were also observed between the two ecosystems, during the rainy season. For the Pantanal, soil oxygen (2) tended to be higher in the rainy season, while having higher peaks in this period. In general, in the Pantanal, the soil temperature averages were higher most of the time, and in relation to soil moisture, the highest averages were observed in the dry period, when compared to the Cerrado. It is possible to observe higher averages of net 2 exchanges in the Pantanal, especially in periods of drought, with some inversions for the Cerrado occurring in the rainy season. In the months of May and June of the 2nd year, there were higher NEE peaks in the Cerrado, and in the months of April to October of the 3rd year, there were much smaller peaks than those observed in the Pantanal. In general, GPP averages were higher in the Pantanal, with higher values in dry periods. It was possible to infer that the micrometeorological and soil variables that most influence NEE, GPP and ET among the studied biomes are different. The data also show a tendency to maintain, in the Pantanal, an always high ET throughout each year, regardless of the rainy or dry season, and at certain times the ET value in the Pantanal is twice that measured in the Cerrado.